The Osteogenic Effect of Local Delivery of Vancomycin and Tobramycin on Bone Marrow Stromal Cells - Yu, Lingjia (Infect Drug Resist, 2020)
PURPOSE: Bone tissue infections are a difficult problem in orthopedic surgery. Topical application of vancomycin and tobramycin powder has been proved to significantly reduce infection rates. However, the osteogenic effect of the topical application of these two antibiotics is unclear. In this study, the osteogenic effect of local delivery antibiotics on bone regeneration was investigated in vitro. METHODS: Bone marrow stromal cells (BMSCs) were incubated in the presence of vancomycin (14.28μg/mL), tobramycin (28.57μg/mL), or vancomycin combined with tobramycin (vancomycin 14.28μg/mL and tobramycin 28.57μg/mL). Cell viability, proliferation, and migration were analyzed. The alizarin red staining as well as the alkaline phosphatase staining was investigated. Then, the quantitative real-time (qRT)-PCR of osteogenic mRNA expression levels were also evaluated. RESULTS: The results showed that vancomycin combined with tobramycin has no adverse effect on the viability and proliferation of BMSCs. The topical application of vancomycin alone may interfere with the bone regenerative processes. However, the tobramycin can promote the osteogenic differentiation of BMSCs and also rescue the osteogenic potential of BMSCs inhibited by vancomycin both in vitro. CONCLUSION: From this in vitro study, local application of vancomycin combined with tobramycin does not affect the osteogenic potential of BMSCs.